2003
DOI: 10.1242/dev.00544
|View full text |Cite
|
Sign up to set email alerts
|

A temperature-sensitive mutation in thenodal-related genecyclopsreveals that the floor plate is induced during gastrulation in zebrafish

Abstract: The floor plate, a specialized group of cells in the ventral midline of the neural tube of vertebrates, plays crucial roles in patterning the central nervous system. Recent work from zebrafish, chick, chick-quail chimeras and mice to investigate the development of the floor plate have led to several models of floor-plate induction. One model suggests that the floor plate is formed by inductive signalling from the notochord to the overlying neural tube. The induction is thought to be mediated by notochord-deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 59 publications
3
35
0
Order By: Relevance
“…Although Cyc and Sqt share 68% identity and 78% sequence similarity in their mature domains, their pro-domains are more divergent (Erter et al, 1998;Rebagliati et al, 1998a). In particular, the Cyc pro-domain has several proline-rich regions that are not shared by any of the other vertebrate Nodal-related factors (Hudson and Yasuo, 2005;Jones et al, 1995;Morokuma et al, 2002;Rebagliati et al, 1998a;Sampath et al, 1998;Tian et al, 2003;Toyama et al, 1995;Yu et al, 2002;Zhou et al, 1993). Although it is not clear how this region evolved, the presence of the proline-rich repeats is suggestive of insertion by (Constam and Robertson, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Cyc and Sqt share 68% identity and 78% sequence similarity in their mature domains, their pro-domains are more divergent (Erter et al, 1998;Rebagliati et al, 1998a). In particular, the Cyc pro-domain has several proline-rich regions that are not shared by any of the other vertebrate Nodal-related factors (Hudson and Yasuo, 2005;Jones et al, 1995;Morokuma et al, 2002;Rebagliati et al, 1998a;Sampath et al, 1998;Tian et al, 2003;Toyama et al, 1995;Yu et al, 2002;Zhou et al, 1993). Although it is not clear how this region evolved, the presence of the proline-rich repeats is suggestive of insertion by (Constam and Robertson, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Capped mRNA was synthesized from linearized plasmids using the mMessage mMachine kit (Ambion), and 0.5 pg, 1.25 pg, 5 pg or 25 pg aliquots of capped mRNA were injected into zebrafish embryos at the one-cell stage. The embryos were fixed in 4% paraformaldehyde (PFA) at 50% epiboly and processed for in situ hybridization to detect gsc or ntl expression (Tian et al, 2003). For detecting the range of signaling, 5 or 10 pg aliquots of in vitro synthesized capped mRNA encoding Sqt, Cyc, CycΔ2, Cyc pro :Sqt mat , Sqt pro :Cyc mat , Sqt Cyc2 :Sqt were injected together with the lineage tracers fluorescein-dextran and biotinylated dextran (Molecular Probes) into a single cell of 64-to 128-cell zebrafish wild-type embryos.…”
Section: Zebrafish Embryo Injectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole-mount in situ hybridization was performed as described (Tian et al, 2003). The following plasmids were linearized and antisense probes were synthesized by in vitro transcription: pBSints5 (BamHI, T3 RNA Polymerase), pGEMT-Easyscl (NcoI, SP6 RNA Polymerase), pBSgata1 (XbaI, T7 RNA Polymerase), pBSflk1 (SmaI, T7), pKSpax2a (BamHI, T7) (Detrich et al, 1995;Gering et al, 1998;Liao et al, 1997;Majumdar et al, 2000), pBShgg1 (XbaI, T7) (Thisse et al, 1994), pBSgsc (EcoRI, T7) (Thisse et al, 1994), pBSntl (XhoI, T7) (Schulte-Merker et al, 1994), pBSspt (EcoRI, T7) (Griffin et al, 1998), pBSsox17 (EcoRI, T7) (Alexander and Stainier, 1999), pBSmyoD (BamHI, T7) (Weinberg et al, 1996) and pBSdlx3 (SalI, T7) (Akimenko et al, 1994).…”
Section: In Situ Hybridization Analysesmentioning
confidence: 99%
“…In zebrafish, mutant analyses and lineage tracing have shown that MFP cells originate from a pool of midline precursor cells in the gastrula organizer, the embryonic shield (Appel et al 1999;Le Douarin and Halpern 2000). Accordingly, the induction of the MFP in zebrafish occurs during gastrulation by shield-derived factors (Tian et al 2003). Initially induced MFP precursors persist in the tailbud and contribute to the MFP during later embryonic development.…”
mentioning
confidence: 99%